Analysis of Trade Goods Inventory Valuation at Tb. Rizky Mandiri Door - Fitriani, Kamila; Mohammad Darul Fadli, Uus; Ery , Rosmawati (Research in Management of Technology and Business, 2024)
Trade inventory is a collection of goods the company sells to customers. The main source of company income is inventory. This study aimed to know the recording and valuation of trade goods inventory and how the inventory method compares with the FIFO and the LIFO methods. This research is quantitative descriptive research. This research place is located at TB. Pintu Rizky Mandiri Tanjungmekar, West Karawang District. The informants in this study were shop owners. Primary data was collected from observation, interviews, and documentation, and secondary data was obtained through books, previous research, online media, and libraries. The results showed that valuing trade goods inventory using the FIFO method is more efficient than using the LIFO method because the FIFO method results in a low cost of goods sold compared to using the LIFO method.